2023
DOI: 10.3390/molecules28155820
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Different Bilberry (Vaccinium myrtillus L.) Extracts on Human Salivary α-Amylase

Abstract: Recently, consumer preferences for bilberries have increased markedly. This fact is probably related to their natural constituents, such as phenolic compounds including anthocyanins and tannins, as well as the vitamins and minerals they contain. Phenolic compounds are known for their numerous beneficial effects on human health. Moreover, bilberry fruits have been shown to inhibit the activity of carbohydrate hydrolyzing enzymes, which can significantly decrease the postprandial increase in blood glucose levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The α-amylase inhibition activity concentrations of α-amylase inhibitors in freezedried extracts were generally lower than those of ethanol extracts. The most effective inhibitors were found in freeze-dried VV aerial parts S and ethanol extracts of VV aerial parts D. Furthermore, according to Karcheva-Bahchevanska et al, the obtained data indicate no significant difference between the VM berries and leaves [10]. Therefore, leaves or aerial parts can serve as substitutes for berries.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The α-amylase inhibition activity concentrations of α-amylase inhibitors in freezedried extracts were generally lower than those of ethanol extracts. The most effective inhibitors were found in freeze-dried VV aerial parts S and ethanol extracts of VV aerial parts D. Furthermore, according to Karcheva-Bahchevanska et al, the obtained data indicate no significant difference between the VM berries and leaves [10]. Therefore, leaves or aerial parts can serve as substitutes for berries.…”
Section: Discussionmentioning
confidence: 87%
“…Finding such inhibitory effects in VM and VV extracts could potentially slow down the digestion of carbohydrates, resulting in a slower release of glucose into the bloodstream [10]. This could be beneficial for individuals with T2DM by helping to manage blood sugar levels [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current in vitro and animal studies have shown that anthocyanins are effective carbohydrate digestive enzyme inhibitors [ 13 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. These mechanisms undoubtedly play a crucial role in their anti-diabetic properties, thereby reducing postprandial blood glucose levels.…”
Section: Recent Advances In Understanding Dietary Anthocyanins’ Anti-...mentioning
confidence: 99%
“…In the last few years, the development of polyphenol research concerning their impact on diabetes has markedly progressed. Numerous in vivo and in vitro studies provide knowledge for a better understanding of the role of nutrition and its impact on diabetes treatment [ 11 , 12 , 13 , 14 ]. Natural compounds, such as flavonoids, have been extensively researched for their ability to target glucose metabolism and inflammatory processes by influencing signaling cascades and immune system cell responses [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%